Attitudes and experiences of European clinical geneticists towards direct-to-consumer genetic testing: a qualitative interview study. Issue 4 (2nd October 2019) - Kalokairinou, Louiza; Borry, Pascal; Howard, Heidi C.
Abstract : Direct-to-consumer (DTC) genetic tests (GT) enable consumers to access a wide range of GT, without involving a healthcare professional, promoting an increasing disassociation of genetics from the clinical context. This study explores, through semi-structured interviews, the experiences and attitudes of European clinical geneticists towards DTCGT. Our results indicate that the participants have limited experience of consultations with patients regarding such tests. The majority of participants stated that consumers purchased tests out of curiosity and sought a general interpretation of test results by a healthcare professional. Most respondents were skeptical of the quality of tests, especially regarding their clinical utility. The participants supported the importance of medical supervision and genetic counseling in this context. Finally, most respondents considered it their duty to accept consultations concerning DTCGT results. However, due to concerns over limited time and potential downstream costs, some participants supported that a prioritization system based on guidelines would be necessary.